2022
DOI: 10.4266/acc.2022.00528
|View full text |Cite
|
Sign up to set email alerts
|

Early mechanical ventilation for grade IV hepatic encephalopathy is associated with increased mortality among patients with cirrhosis: an exploratory study

Abstract: Background: Unresponsive patients with toxic-metabolic encephalopathies often undergo endotracheal intubation for the primary purpose of preventing aspiration events. However, among patients with pre-existing systemic comorbidities, mechanical ventilation itself may be associated with numerous risks such as hypotension, aspiration, delirium, and infection. Our primary aim was to determine whether early mechanical ventilation for airway protection was associated with increased mortality in patients with cirrhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The need for airway protection due to hepatic coma and respiratory failure resulting from lung infection, pleural effusion, hepatopulmonary syndrome, etc. , are the main reasons why liver cirrhosis patients are admitted to the ICU for respiratory support[ 36 , 37 ]. Mechanical ventilation has been demonstrated to be associated with poorer prognosis in several studies[ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need for airway protection due to hepatic coma and respiratory failure resulting from lung infection, pleural effusion, hepatopulmonary syndrome, etc. , are the main reasons why liver cirrhosis patients are admitted to the ICU for respiratory support[ 36 , 37 ]. Mechanical ventilation has been demonstrated to be associated with poorer prognosis in several studies[ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…And researchers also found that the use of mechanical ventilation was a significant risk factor for mortality [ 37 ]. The study by Saffo S et al has demonstrated that mechanical ventilation was the strongest predictor of in-hospital mortality in their primary analysis (OR, 3.00; 95% CI, 2.14–4.20; P < 0.001) and in all sensitivity analyses [ 38 ]. Studies by Benhaddouch Z et al came to similar conclusion [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential benefit of early endotracheal intubation in those with grade IV hepatic encephalopathy is uncertain, although the high mortality risk may be a function of the severity of liver disease and not necessarily that of the grade of HE. 55 Lung-protective techniques can be used in critically ill patients with cirrhosis, especially in the setting of ARDS. In patients without ARDS, low tidal volume ventilation at 6 mL/kg predicted body weight (PBW) versus 10 mL/kg PBW showed no difference in outcomes, provided that the plateau pressure was maintained below 25 cm H 2 O.…”
Section: Outcomes In Mechanically Ventilated Patients With Cirrhosismentioning
confidence: 99%
“…Intubation within the first two hospital days was linked to a 40% mortality rate, compared to 19% in non‐ventilated patients. Thus, the potential benefit of early endotracheal intubation in those with grade IV hepatic encephalopathy is uncertain, although the high mortality risk may be a function of the severity of liver disease and not necessarily that of the grade of HE 55 …”
Section: Introductionmentioning
confidence: 99%